(untitled) (CIPEEX, 2025)
This paper analyzes the equivalence of the crime of racial injury to racism for the purposes of imprescriptibility, made by the Supreme Court in the trial of Habeas Corpus nº 154,248, with the consequences in the edition of Law nº 14,532/2023, which amended the Racism Law (Law nº 7.716/1989), incorporating the new jurisprudential position. The Supreme Court has adopted several interpretations applying to cases of general repercussion. Through a qualitative approach and deductive method, the work analyzes the legislation, doctrines and jurisprudence to understand the classification of the crime of racial injury as a modality of the crime of racism. As a result of this research, it was noticed that the decisions of the Supreme Court have a clear reflection not only in the jurisprudential interpretation, but also in the edition of new laws, as in the case analyzed, Law nº 14.532/2023, which amended Law nº 7.716/1989, which deals with the definition of crimes resulting from color or race prejudice and other forms of discrimination.